1980
DOI: 10.7326/0003-4819-93-3-399
|View full text |Cite
|
Sign up to set email alerts
|

Leukocyte Interferon-Induced Tumor Regression in Human Metastatic Breast Cancer, Multiple Myeloma, and Malignant Lymphoma

Abstract: Thirty-eight patients with advanced breast cancer, multiple myeloma, and malignant lymphoma were treated with partially purified (about 0.1%) leukocyte interferon. Patients were treated with a remission-induction schedule of 3 million to 9 million antiviral units daily intramuscularly for 4 to 26 weeks. Responding patients were maintained on a schedule of 3 million U three times weekly. Tumor regression was observed in seven of 17 patients with breast cancer. Six of 10 patients with multiple myeloma responded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
87
1
1

Year Published

1982
1982
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 471 publications
(92 citation statements)
references
References 17 publications
3
87
1
1
Order By: Relevance
“…Early reports of encouraging objective response rates for alpha interferons in breast carcinoma (Borden et al, 1982;Gutterman et al, 1980) have not been repeated in our own experience (Table II). This discrepancy may in part reflect the predominance in our study of late stage patients.…”
Section: Resultsmentioning
confidence: 92%
“…Early reports of encouraging objective response rates for alpha interferons in breast carcinoma (Borden et al, 1982;Gutterman et al, 1980) have not been repeated in our own experience (Table II). This discrepancy may in part reflect the predominance in our study of late stage patients.…”
Section: Resultsmentioning
confidence: 92%
“…Recent results suggest that treatment of some tumour types with various preparations of Interferon (IFN) might result in occasional clinical success (Gutterman et al, 1980). Experimental support for this suggestion derives, in part, from the observations that IFNs were found capable of inhibiting the in vitro growth of a wide variety of both normal and malignant cell types (Balkwill & Oliver, 1977).…”
mentioning
confidence: 99%
“…There is evidence that the expression of IRF1 and IRF2 is altered in breast cancer in relation to normal breast tissue (Doherty GM et al 2001). Some studies have shown positive responses in breast cancer treatment when interleukins were used in association with IFN (Gutterman JU et al 1980;Borden EC et al 1982).…”
Section: Breastmentioning
confidence: 99%